FAULT AS A CONDITION OF SANCTIONING ADMINISTRATIVE OFFENCES - Markevičiūtė, Milda (Teisė, 2016)
Administrative offences are to be sanctioned pursuant to two different legal grounds, Code of Administrative Offences (hereinafter – CAO) (after the 1st of January, 2017 will be replaced by the Code of Administrative Violations (hereinafter – CAV)) and special laws, regulating certain economic spheres (hereinafter – Special laws). This rule also determined that sanctioning of administrative offences is to be executed pursuant to different rules, one of such differences – the importance of the element of fault. Both CAO and CAV states the rule that sanctioning of administrative offences is possible only in cases where fault of the person is determined, however, Special laws provides the rule that administrative offences are to be sanctioned pursuant to the rule of objective liability, i.e. the fact of the offence being committed is sufficient enough to presume the fault. In the light of the above, the fault of legal entities as an element of sanctioning administrative offences is being discussed in this article. This element is being analysed in both cases, sanctioning administrative offences pursuant to Code of Administrative Offences and pursuant to special laws regulating certain economic spheres. This category is also being compared with the analogous category in criminal law in order to determine pros and cons. The clauses of the Law on Public Administration related to sanctioning legal entities and the case law are also evaluated. In conclusion, the discussed circumstances are used to conclude that the currently applicable law is not consistent, therefore is to be altered. It is also suggested to amend the Law on Public Administration, defining that that legal entities are to be sanctioned only where the fault are determined, in respect to be objective circumstances.